Parcerias Estado e organizações especializadas : discursos e práticas em nome da integração/inclusão educacional das pessoas com deficiência - Araújo, Edgilson Tavares de (2006)
The proposal of this dissertation was to analyze the State and civil society speeches and practices. It is related to planning and management of partnerships directed to the educational attendance of people with disability, after the Lei das Diretrizes e Bases da Educação Nacional / 1996 (Law of Policies and Standards of the National Education). In the context of ambiguities in public and private relationships, it was evaluated the way by which inclusion and integration proposals had been used for partnerships accomplishment between the Secretaria de Educação Especial / Ministério da Educação SEESP / MEC (Special Education Secretary / Education Ministry) and specialized organizations. By means of historical rescue of the facts that occurred in this area, it was possible to analyze the law impacts in the educational scope between 1996 and 2006, as well as evaluate the Special Education Policy execution and the proposals for inclusive education. It shows their main challenges and possibilities. The nature of methodology used is qualitative, considering also quantitative secondary data, documental reviewing, official statistics and interviews with managers of SEESP/MEC and specialized organizations. The data has been systemized using the technique of content analysis and thematic categorical analysis. The results point out the occurrence periods of greater or lesser approach and retraction between State and specialized organizations, as well as the types of the amplified or prompt partnerships. Convergent speeches are identified: concerning special education resignation and the roles of specialized schools, the super-valorization of the constitutive legality, constituted legitimacy of the specialized organization, the abstract morals of inclusion and the instrumental aspects required to pedagogical and management processes. The study was concluded pointing out the main dilemmas and present challenges between State and civil society for changing in the partnerships scenes, in order to guarantee the subjective right of education to people with disability: vision about education, concept of inclusion, comprehension about the public arena, special education and inclusion relationship, legislation interpretation, inter-sectorials relationships, financing, policies and management partnerships